2017
DOI: 10.5194/wes-2016-57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flow angle measurement of a yawed turbine and comparison to models

Abstract: Abstract. The torque generated by a wind turbine blade is dependent on several parameters, one of which is the angle of attack.Several models for predicting the angle of attack in yawed conditions have been proposed in the literature, but there is a lack of experimental data to use for direct validation.To address this problem, experiments were conducted under controlled conditions at the University of Waterloo Wind Generation Research Facility using a 3.4 m diameter test turbine. A five-hole pressure probe wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…. This wide range of α was chosen to replicate the same range that wind turbine blades experience [43,44]. Both coefficients are determined by integrating the differential coefficient of pressure (∆(C p )) along the chord of the airfoil from the 27 differential pressure transducers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…. This wide range of α was chosen to replicate the same range that wind turbine blades experience [43,44]. Both coefficients are determined by integrating the differential coefficient of pressure (∆(C p )) along the chord of the airfoil from the 27 differential pressure transducers.…”
Section: Resultsmentioning
confidence: 99%
“…Morote [41] and Burton et al [42] modeled the α variation as a function of azimuthal position. Gallant and Johnson [43] compared those previous two models to experimental data on a 3.4 m diameter HAWT. From the models and experiments it was found that the α variation is very similar to a sinusoidal path when the turbine is yawed.…”
Section: B Airfoil Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results published by Gallant and Johnson (2017) indicate that when an operating wind turbine is yawed, the mean oscillating α could be 25 • while the amplitude could be 5 • under certain conditions. Case 2 in this paper aims to simulate a wind turbine blade under the same conditions mentioned in Gallant and Johnson.…”
Section: Dynamic Pitchingmentioning
confidence: 99%
“…In some operating conditions, a percentage of the wind turbine blade span could be experiencing α values higher than 30 • . Gallant and Johnson (2017) measured α on a wind turbine blade operating under yaw conditions to be oscillating around a mean α of 25 • with an amplitude of 5 • . Most of the papers and references presented so far study the dynamic stall cycle where the maximum pitch angle is 25 • .…”
Section: Introductionmentioning
confidence: 99%